2021
DOI: 10.18510/hssr.2021.9353
|View full text |Cite
|
Sign up to set email alerts
|

Dividend Policy, Corporate Governance and Earnings Quality: A Case of Non-Financial Listed Firms of Pakistan

Abstract: Purpose of the study: This research empirically examined the impact of the dividend policy and corporate governance attributes (board size, board meetings, audit quality, nomination committee, board independence, remuneration committee, and CEO duality) on earnings quality (EQ) of the firms in Pakistan. Methodology: The study used secondary data of 148 non-financial listed companies of the Pakistan Stock Exchange (PSX) with 1450 firm-year observations over 10 years from 2010 to 2019. Earning quality was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Andriana et al (2021) also explored these factors' importance in predicting profit quality and found a positive correlation between higher-quality profits and profitability, scale, and investment prospects. Afzal et al (2021) found no significant impact of dividend policy on earnings quality. Compensation committee and audit quality positively affected earning quality but negatively affected earning management.…”
Section: Introductionmentioning
confidence: 86%
“…Andriana et al (2021) also explored these factors' importance in predicting profit quality and found a positive correlation between higher-quality profits and profitability, scale, and investment prospects. Afzal et al (2021) found no significant impact of dividend policy on earnings quality. Compensation committee and audit quality positively affected earning quality but negatively affected earning management.…”
Section: Introductionmentioning
confidence: 86%
“…So the DP and EM are interrelated. However some authors elucidate no connection amongst EQ & dividends (Afzal et al, 2021;Grullon et al, 2005;Mousa & Desoky, 2019). The outcomes of their studies recommended that dividend do not forecast the future incomes of the corporations and have no connections with earning management.…”
Section: Dividend Policy and Earnings Qualitymentioning
confidence: 99%
“…But in developing economies, particularly Pakistan there is limited empirical evidence in this connection. Recently a research conducted in this regard elucidated that DP & EQ are not significantly related, however the attributes of corporate governance influences the earnings management practices (Afzal, Siddiqui, Khan, Khan, & Huseen, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the research earnings quality has always been highly discussed. From the perspective of external corporate governance, surplus management of listed companies in various countries is unique due to different legal environments and investor protection mechanism [15]. From the perspective of internal corporate governance, the higher the level of corporate governance, the higher the earnings quality [15,16].…”
Section: Literature Review Of Earnings Qualitymentioning
confidence: 99%
“…From the perspective of external corporate governance, surplus management of listed companies in various countries is unique due to different legal environments and investor protection mechanism [15]. From the perspective of internal corporate governance, the higher the level of corporate governance, the higher the earnings quality [15,16]. In addition, both non-executive directors and outside independent directors have the abilities to improve earnings quality [17].…”
Section: Literature Review Of Earnings Qualitymentioning
confidence: 99%